A Non-Conventional Interaction on Computational Systems Based on Mouth Puffing - M. Campos, Erick; A. Freitas, Alexandre; F. Cunha, Renan; T. Batista, Cassio; S. Meiguins, Bianchi; C. Sampaio Neto, Nelson (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
Computer mice and keyboards have for long been the dominant input devices for desktop computers. Nonetheless, they still represent quite a barrier — especially for people whose upper-limb motor skills are compromised. This work proposes a low-cost, mouth-puffing-based device that is able to perform the mouse click on computational platforms. Additionally, a driver was developed to allow the device to communicate with the computer via audio jack P2 interface. The mouse cursor is controlled by head tracking thanks to eViacam software. The evaluation took place by comparing the proposed equipment with the dwell time method on navigation tasks elaborated over websites.